1974
DOI: 10.1099/00221287-80-1-253
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH, Germinants and Temperature on the Germination of Spores of Clostridium bifermentans

Abstract: S U M M A R YThe germination rate of Clostridicinz bifermentans spores and the manner in which it is influenced by pH, sodium ion concentration and temperature differ according to the organic germinant used. Only L-alanine initiated germination when present alone. The germination rate with optimal L-alanine was increased by L-phenylalanine, L-arginine, L-histidine or L-lysine but not by other common amino acids or L-lactate. With suboptimal concentrations of L-alanine, addition of L-lactate, L-arginine or L-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…The study of outgrowth at different temperatures, showed that spores of C. bifermentans were able to swell at 50 "C but that elongation only occurred below 49 "C. Previously, we have found that germination would occur up to 61 "C (Waites & Wyatt, 1974). In similar experiments, Levinson & Hyatt (1970) found that spores of Bacillus megaterium germinated at 50 "C but only outgrew below 47 "C. It is apparent that the later the event during germination and outgrowth the more sensitive it is to high temperatures, presumably because the metabolic requirements for the later stages of development are more heat sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of outgrowth at different temperatures, showed that spores of C. bifermentans were able to swell at 50 "C but that elongation only occurred below 49 "C. Previously, we have found that germination would occur up to 61 "C (Waites & Wyatt, 1974). In similar experiments, Levinson & Hyatt (1970) found that spores of Bacillus megaterium germinated at 50 "C but only outgrew below 47 "C. It is apparent that the later the event during germination and outgrowth the more sensitive it is to high temperatures, presumably because the metabolic requirements for the later stages of development are more heat sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Germination of this strain of C. bifermentans will occur at up to 6 1 "C (Waites & Wyatt, 1974) and it was of interest to determine whether outgrowth would occur at similar temperatures. Turbidity increases were measured at temperatures of up to 47 "C but microscopic examination showed that spore swelling and elongation were slower at 47 "C than at 37 "C, and that fewer spores were able to elongate (Table I).…”
Section: Determination Of Conditions For Outgrowthmentioning
confidence: 99%
“…4). It is thought that the spore coats protect spores against lysis and killing by chemical agents or lytic enzymes (2,6,7,14,27,29). Studies on the ultrastructure of spores treated with various chemicals demonstrated modification of the coats leading to disruption of normal permeability barriers (15,20,26) ; moreover, disintegration of the coats resulted in inactivation of the spores (18).…”
Section: Discussionmentioning
confidence: 99%
“…Waites et al (27) found that alkali treatment of spores altered their quantitative and qualitative requirements for induction of germination, and decreased the electron density of the spore coats but had no effect on protoplasts. Gould and Hitchins (6) found that spores became sensitive to lysozyme when pretreated with thioglycolate at pH 3, and suggested that resistance of spores to the lytic enzyme was due to the impermeability of the coat to this protein.…”
mentioning
confidence: 99%
“…Spore suspensions were fixed with buffered 3 % (v/v) glu taraldehyde for 3 h (without any subsequent fixation with osmium tetroxide) before washing overnight in buffer (Gordon et al, 1963). Samples were then dehydrated and embedded, and sections were examined with or without staining with uranyl acetate and lead acetate as described previously (Waites et al, 1972).…”
mentioning
confidence: 99%